The Food Mafia as Food Cartels under Competition Law:An Analysis of KPPU Decisions in the Staple Food Sector - Tanudjaja; Arief Budiman; Golkar Pangarso Rahardjo Winarsadi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The term food mafia is a popular expression that refers to the control of supply chains and prices of essential food commodities by a coordinated group of business actors. From the perspective of competition law in Indonesia, this practice closely resembles the structure and behavior of a cartel, which is clearly prohibited under Law Number 5 of 1999. This article examines the extent to which food mafia practices can be classified as food cartels within the legal framework of competition law, and how the Business Competition Supervisory Commission (KPPU) has proven and addressed these practices in its decisions. Using a normative juridical method with a legal and case study approach, this research focuses on two major decisions: Number 24 KPPU I 2009 on the cooking oil cartel and Number 05 KPPU I 2013 on garlic importation. The analysis shows that food mafia practices can be legally framed as cartels when evidence of agreement or coordinated conduct among business actors is established. However, complex regulations and limited evidentiary tools pose challenges for law enforcement. The study concludes that the cartel framework is important for explaining the food mafia phenomenon, but its effectiveness depends on the strength of economic and legal proof built by KPPU, as well as more coherent regulations to support consumer protection and food security.